Quando Oswald devorou o crítico Maupassant - das Neves, Angela (FronteiraZ. Revista do Programa de Estudos Pós-Graduados em Literatura e Crítica Literária, 2012)
Oswald de Andrade, idealizer of the Modern Art Week of 1922 and one of the main epigones of the Brazilian Modernismo, is known by being a detractor of the veneration for the literary past. His activity of journalist kept him close to the daily task of writing on and thinking about what was happening around him and he did not save constant criticism of the European cultural loans. The reading of his works, that include dramatic texts, novels, poetry, chronicles, essays and memories, allows us to see, however, that the modern writer not only had a loving relation with the biographical and aesthetic plan with France, but also did not hesitate in apprehending and transposing artistic concepts that came from there. One of his articles, entitled Questions of Art – of which we will occupy here –, if on one hand discloses diverse of the aesthetic and nationalistic concerns of the intellectual to the eves of the Modern Art Week, on the other hand opens a rich dialogue with a critical text of the French writer Guy de Maupassant, the essay Le roman. Questions of Art, which has not been republished since its first version for the Jornal do Commercio of São Paulo, in 1921, discloses to interesting oswaldians commentaries on literature and arts, that anticipate ideas later developed by Oswald in several other texts. We not only intend to bring to knowledge this important article of Oswald de Andrade, forgotten in the editions of his collected works, but also to reopen his questioning on the important essay of Guy de Maupassant, considered for some scholars as Maupassant’s Poetical Art.